Adverse childhood experiences, alcohol consumption, and the modifying role of social participation: population-based study of adults in southwestern Uganda - Ashaba, Scholastic; Kakuhikire, Bernard; Baguma, Charles; Satinsky, Emily N.; Perkins, Jessica M.; Rasmussen, Justin D.; Cooper-Vince, Christine E.; Ahereza, Phionah; Gumisiriza, Patrick; Kananura, Justus; Bangsberg, David R.; C. Tsai, Alexander (SSM-mental health, 2022)
Background: Adverse childhood experiences (ACEs) include multiple forms of child maltreatment, including abuse and neglect, as well as other forms of household dysfunction. Studies from Uganda have revealed a high prevalence of child abuse, as well as one of the highest levels of alcohol consumption in Africa. Few population-based studies from Africa have estimated associations between ACEs and adult alcohol use, or assessed the potential buffering effects of social participation. Methods: This cross-sectional, population-based study was conducted in a rural parish in southwestern Uganda between 2016 and 2018. We assessed self-reported ACEs using a modified version of the Adverse Childhood Experiences – International Questionnaire (ACE-IQ) scale. We measured heavy alcohol consumption using a 3- item scale previously validated in this population. We measured social participation using a 10-item scale eliciting participants’ membership and participation in different community groups over the past two months. We fitted multivariable Poisson regression models to estimate the associations between ACEs and heavy alcohol consumption, and to assess for the potential buffering effects of social participation. Results: We estimated statistically significant associations between the total ACE score and heavy alcohol consumption (adjusted relative risk [ARR] per ACE ¼ 1.17; 95% CI, 1.09–1.25; P _ 0.001). Social participation had a statistically significant moderating effect on the association between total ACE score and heavy alcohol consumption (P ¼ 0.047 for interaction): the estimated association between total ACE score and heavy alcohol consumption among study participants who did not participate in a community group was larger, with a narrower confidence interval (ARR ¼ 1.21 per ACE; 95% CI, 1.11–1.33; P < 0.001), while the estimated association among study participants who did participate in a community group was smaller and less precisely estimated (ARR ¼ 1.12 per ACE; 95% CI, 1.02–1.24; P ¼ 0.02). Conclusions: Our findings demonstrate an association between ACEs and heavy alcohol consumption behavior among adults in rural Uganda. The adverse effects of ACEs were buffered in part by social participation. To prevent or reduce harmful alcohol use behaviors among adults, it is important to address the chronic stress caused by ACEs.
Keywords: Buffering hypothesis; Heavy alcohol consumption; Social integration; Social participation; Stress buffering; Sub-Saharan Africa; Uganda